Assessment and correction of the geriatric status of patients with metastatic colorectal cancer during the first-line systemic therapy - Yuliia V. Alekseeva (IP Habib O.N., 2021)
Humanity is rapidly aging, about 50% of all human malignancies develop in people over 65 years old. Cancer and antineoplastic therapy are potential pathophysiological stressors that worsen the course or intensify the development of previously compensated comorbidities and geriatric syndromes. At present, the role of assessment and correction of geriatric syndromes (CGS) for the purpose of effective first-line drug therapy in patients with metastatic CRC in the elderly and senile age, based on the use of a comprehensive geriatric assessment, has not been evaluated.